SELECTIVITY OF INSETICIDES USED IN CONTROL OF FALL ARMYWORM FOR EGGS AND NYMPHS OF Doru luteipes - REDOAN, ANA CAROLINA MACIEL; CARVALHO, GERALDO ANDRADE DE; CRUZ, IVAN; FIGUEIREDO, MARIA DE LOURDES CORRÊA; SILVA, RAFAEL BRAGA DA (International Journal of Maize & Sorghum, 2012)
Doru luteipes (Scudder, 1876) (Dermaptera: Forficulidae) is considered an efficient predator and recent studies have shown the possibility of using the natural enemy to control Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) in maize (Zea mays L.). The aim of this was to evaluate the effects of insecticides registered for the control of S. frugiperda in crop corn on eggs and first instars of the predator D. luteipes. We evaluated the viability of eggs treated with insecticides and insect survival rate in each instar. After 96 hours after onset of exposure, all insecticides were classified as harmful (class 4) for the first instars of D. luteipes. As for the egg viability of D. luteipes, triflumuron, thiamethoxan/λ-cyhalothrin and teflubenzuron/α-cypermethrin were toxic (class 4); clofenapir and spinosad slightly harmful (class 2) and etofenprox harmless (class 1). All insecticides evaluated showed no physiological selectivity to nymphs of D. luteipes and should be evaluated under semi-field and field to verify the existence of other types of selectivity.